Observational Study of Drug Formulation Manipulation in Pediatric Versus Adult Inpatients. Issue 1 (January 2021) - Spishock, Samantha; Meyers, Rachel; Robinson, Christine A.; Shah, Pooja; Siu, Anita; Sturgill, Marc; Kimler, Katelin
Abstract : Objectives: Medications often require manipulations to measure and administer the correct dose for pediatric patients. These manipulations pose medication safety risks. The objective of this study was to determine the frequency of drug formulation manipulations in the pediatric inpatient population and compare the findings to a parallel adult inpatient population. Methods: Observations were conducted at four sites with 1 day of data collection per week by a randomized schedule for 5 weeks. All pediatric inpatients at each study site were included as well as an equivalent number of medication orders from adult inpatients with similar levels of care. The percentage of medication orders requiring a manipulation were evaluated and compared between pediatric and adult patients. Results: A total of 15, 722 medication orders were analyzed. Drug formulation manipulation was required in 3925 (49.9%) of 7861 pediatric orders versus 1301 of 7861 adult orders (16.6%) ( P < 0.05). By pediatric service, drug manipulations were required most frequently (71.5% of orders) in the neonatal intensive care unit. The most common dosage forms requiring manipulation for pediatric patients were oral liquids (45.7% of orders) and intravenous medications (44.6% of orders). By pediatric patient age, drug manipulation was required most often in patients aged 1 to 12 months (69.8% of orders). Conclusions: Drug formulation manipulation was three times more common in pediatric inpatient practice compared with adult inpatient practice in this study. This study demonstrated a statistically significant difference in the prevalence of drug formulation manipulation between pediatric and adult inpatients.